Child Adoption Without a Judicial Process in Sawentar Village, Blitar Regency (Perspective of Positive Law and Islamic Law) - Amanu, Damar; Azizah, Aisyatul; Laili, Afrohatul; Tertibi, Yaoma (Universitas Muhammadiyah Surakarta, 2024)
In Islam, adopting children has been known since the time of the Prophet Muhammad. Literally, tabbani means a family couple who tries to get a foster child from another family, then treats it as if it were their biological child. The reality of informants in Sawentar, Blitar, child adoption is based on the agreement of biological parents with adoptive parents, then the adopted child is manipulated as if he were the biological child of the adoptive parents, without going through the court process, Research qualitative approach type of observational research, field-research, determination of empirical approaches, subjected to 3 primary sources. Descriptive qualitative means using qualitative data, then described descriptively. Problems are solved by non-doctrinal empirical normative studies, sourced from primary and secondary data. The purpose of the research is to describe the process of adoption without trial, under HI / Islamic Law and or HP / Positive Law. Documentation, data collection by interviewing, observing reinforced the technique of analyzing documents in the design of descriptive qualitative methods, starting with reducing, presenting, ending with drawing conclusions, where the researcher holds the primary key. The conclusion was found that child adoption in Sawentar Village, the subject of the study carried out the adoption without going through the procedures as established by the government. This means that in positive law there is a violation of the law. The subject considers the judicial procedure to be a lot of time consuming, feels the complexity, does not meet the requirements of adoption, and the lack of understanding regarding child adoption according to the law. Implications, reviewing positive law, judicial child adoption is not fulfilled, if the socialization of adoption in the community is not intensified. Adoption is more about the agreement of both parties without a court process. Then, there is a lack of legal protection for adopted children, confidentiality in both, if not open, nasab (family ties based on blood relations, both up, down, and sideways) and the pleasure of the mother, father or biological person will be lost.